Surgical versus non-surgical approach in primary desmoid-type fibromatosis patients: A nationwide prospective cohort from the French Sarcoma Group. (September 2017) - Penel, Nicolas; Le Cesne, Axel; Bonvalot, Sylvie; Giraud, Antoine; Bompas, Emmanuelle; Rios, Maria; Salas, Sébastien; Isambert, Nicolas; Boudou-Rouquette, Pascaline; Honore, Charles; Italiano, Antoine; Ray-Coquard, Isabelle; et al.
Abstract: Purpose: The outcome of desmoid-type fibromatosis (DTF) is unpredictable. Currently, a wait-and-see approach tends to replace large en bloc resection as the first therapeutic approach. Nevertheless, there are no validated factors to guide the treatment choice. Method: We conducted a prospective study of 771 confirmed cases of DTF. We analysed event-free survival (EFS) based on the occurrence of relapse after surgery, progressive disease during the wait-and-see approach, or change in therapeutic strategy. Identification of prognostic factors was performed using classical methods (log-rank test and Cox model). Results: Overall, the 2-year EFS was 56%; this value did not differ between patients undergoing an operation and those managed by the wait-and-see approach (53% versus 58%, p = 0.415). In univariate analysis, two prognostic factors significantly influenced the outcome: the nature of diagnostic sampling (p = 0.466) and primary location (p = 0.0001). The 2-year EFS was only 32% after open biopsy. The 2-year EFS was 66% for favourable locations (abdominal wall, intra-abdominal, breast, digestive viscera and lower limb) and 41% for unfavourable locations. Among patients with favourable locations, the 2-year EFS was similar in patients treated by both surgery (70%) and the wait-and-see approach (63%; p = 0.413). Among patients with unfavourable locations, the 2-year EFS was significantly enhanced in patients initially managed with the wait-and-see approach (52%) compared with those who underwent initial surgery (25%; p = 0.001). Conclusion: The location of DTF is a major prognostic factor for EFS. If these findings are confirmed by independent analysis, personalised management of DTF must consider this easily obtained parameter. Highlights: Primary location is a prognostic factor in desmoid tumour patients. Overall, the wait-and-see policy provides similar outcomes compared with surgery. Surgery is associated with poor outcome in 'favourable' locations. Both the wait-and-see policy and surgery similar outcomes in 'unfavourable' locations.